2015
DOI: 10.1002/asia.201500062
|View full text |Cite
|
Sign up to set email alerts
|

Altering the Position of Phenyl Substitution to Adjust Film Morphology and Memory Device Performance

Abstract: In this study, two structural isomers α-PBT and β-PBT, which only differ in the phenyl substituent position on the quinoline chromophore, have been designed and successfully synthesized. The influences of substituent position on the film morphology and the storage performance of the devices were investigated. Both molecules employed in the memory devices exhibited same nonvolatile binary (write-once-read-many-times; WORM) characteristics, but the switch threshold voltage (Vth) of the β-PBT-based device was cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Encouragingly, both 3- and 4-nitro derivatives displayed impressive nonvolatile memory performance with reasonable endurance and retention time. The literature reveals that structural isomers have rarely been studied to identify the effects of substituent positions on the device behavior and performance. , Additionally, the position of terminal substituents has a significant impact which was evident from the contrasting behavior of the 3- and 4-nitro derivatives (DN3PP, DNPP). While DN3PP exhibited a rewriteable flash memory characteristic, the DNPP exhibited Write Once Read Many time’s (WORM) memory behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Encouragingly, both 3- and 4-nitro derivatives displayed impressive nonvolatile memory performance with reasonable endurance and retention time. The literature reveals that structural isomers have rarely been studied to identify the effects of substituent positions on the device behavior and performance. , Additionally, the position of terminal substituents has a significant impact which was evident from the contrasting behavior of the 3- and 4-nitro derivatives (DN3PP, DNPP). While DN3PP exhibited a rewriteable flash memory characteristic, the DNPP exhibited Write Once Read Many time’s (WORM) memory behavior.…”
Section: Introductionmentioning
confidence: 99%
“…But when they reach the traps, a certain amount of charge gets accumulated inside these traps and needs more electric fields to continue the further transmission of charges. This explains the threshold voltages of the compounds (−1.21 V to −2.12 V) as these charges are trapped in the molecular traps and would require more electric fields to make the movement smoother again [55] . Similarly, these trapped charges cannot be retained quite easily from their traps and consequently, these ON states are stable even after removing the power supply or during the reverse voltage bias.…”
Section: Resultsmentioning
confidence: 99%
“…This explains the threshold voltages of the compounds (À 1.21 V to À 2.12 V) as these charges are trapped in the molecular traps and would require more electric fields to make the movement smoother again. [55] Similarly, these trapped charges cannot be retained quite easily from their traps and consequently, these ON states are stable even after removing the power supply or during the reverse voltage bias. The ground and excited state ESP images of the compounds are given in the Supporting Information along with their dipole moments (Figure S37 and Table S4).…”
Section: Compoundsmentioning
confidence: 99%
“…These results indicate that both amino acids were transformed into the corresponding aldehydes. The user-unfriendly materials phenylacetaldehyde and benzaldehyde together with p -toluidine (1:1:1) as the starting material gave 4a in 57% yield with other inevitable byproducts (Scheme , entry 4) . Compared to the result in standard conditions (Scheme , 77%), this result suggested that the amino groups of amino acid, aniline, and the ammonia which generated in situ from oxidative cleavage promote the transformation through endogenous imine activation process.…”
mentioning
confidence: 92%